Total Saikosaponins of Bupleurum yinchowense reduces depressive, anxiety-like behavior and increases synaptic proteins expression in chronic corticosterine-treated mice - Xiuping Sun; Xianglei Li; Ruile Pan; Yanfeng Xu; Qiong Wang; Mingjing Song (BMC Complementary and Alternative Medicine, 2018)
Abstract Background Bupleurum yinchowense Shan et Y. Li is widely used to treat depressive and anxiety disorders for hundreds of years in China. Total saikosaponins (TSS) is the major ingredient of Bupleurum yinchowense. A-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor and subsequent mammalian target of rapamycin (mTOR) signaling is responsible for synaptic maturation and may contribution to the synaptic alteration underlying depression. The aim of the study was to investigate the antidepressant-like and anxiolytic effect of TSS in chronic corticosterone-treated mice. The effect of TSS on synaptic proteins expression and AMPA receptor-mTOR signaling pathway alteration was also evaluated. Methods Dose-response effect of TSS (12.5, 25, 50 mg/kg) was investigated in forced swim test (FST) in ICR male mice. In the chronic corticosterine-treated model, TSS was given intragastrically once a day for 2 weeks and continued through the behavior testing period. Behavior tests and AMPA receptor related signaling pathway were investigated. Results TSS (25 and 50 mg/kg) decreased the immobility time in the FST when compared with the control group. TSS (25 mg/kg) showed antidepressant-like and anxiolytic effects in the chronic corticosterone treatment model in mice. TSS increased hippocampal synaptic proteins (synapsin-1 and postsynaptic density protein 95) expression. Immunohistochemistry analysis showed that TSS significantly increased the synapsin-1 expression in CA3 of hippocampus. TSS also increased hippocampal phosphorylation expression of GluR1 Ser 845 (AMPA receptor subunit) and its downstream regulators extracellular signaling-regulated kinase (ERK), protein kinase B (Akt) and mTOR. Conclusion TSS produces antidepressant-like and anxiolytic effects and increases synaptic proteins expression which may be mediated by induction of AMPA receptor and subsequent mTOR signaling pathway.